Gas chromatographic identification of Clostridium difficile and detection of cytotoxin from a modified selective medium. - Levett, P N (1985)
A modification of an existing selective medium for Clostridium difficile is described. Inclusion in the medium of DL nor-leucine and p-hydroxyphenylacetic acid enables identification of C difficile to be made directly from primary isolation plates by gas chromatographic detection of caproic acid and p-cresol. Plugs of agar withdrawn from the selective medium also allow the detection of cytotoxin production in vitro.